2021
DOI: 10.3389/fcell.2021.731101
|View full text |Cite
|
Sign up to set email alerts
|

Strong as a Hippo’s Heart: Biomechanical Hippo Signaling During Zebrafish Cardiac Development

Abstract: The heart is comprised of multiple tissues that contribute to its physiological functions. During development, the growth of myocardium and endocardium is coupled and morphogenetic processes within these separate tissue layers are integrated. Here, we discuss the roles of mechanosensitive Hippo signaling in growth and morphogenesis of the zebrafish heart. Hippo signaling is involved in defining numbers of cardiac progenitor cells derived from the secondary heart field, in restricting the growth of the epicardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Besides this, the hippo/YAP1 signaling pathway known to control the transcription of target genes was also shown to be involved in zebrafish Piezo1-dependent aortic valve development [ 46 ]. Valve formation was delayed by Piezo1 knock-down, and the authors observed thicker leaflets than in WT animals [ 31 ].…”
Section: Ion Channels In Aortic Valve Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides this, the hippo/YAP1 signaling pathway known to control the transcription of target genes was also shown to be involved in zebrafish Piezo1-dependent aortic valve development [ 46 ]. Valve formation was delayed by Piezo1 knock-down, and the authors observed thicker leaflets than in WT animals [ 31 ].…”
Section: Ion Channels In Aortic Valve Developmentmentioning
confidence: 99%
“…The Piezo1 knock-out embryo exhibits a reduced expression of YAP1 in the two layers which compose the outflow tract, corresponding to the aortic valve, which is composed of endothelial cells and smooth muscle cells. Piezo1 knock-out embryos also exhibit an increase in the mechano-sensitive transcription factor klf2a [ 31 , 46 ]. This factor is known as a flow-responsive gene in zebrafish as well as in vertebrates [ 33 ].…”
Section: Ion Channels In Aortic Valve Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the underlying reasons is the low predictive value of the commonly used models used in preclinical research ( Eder et al, 2016 ). Although animal models such as mouse, chicken and zebrafish have proven essential for studying the basic principles of cardiogenesis ( Brade et al, 2013 ; Buckingham et al, 2005 ; Kirby, 2007 ; Bornhorst and Abdelilah-Seyfried, 2021 ), their capability to recapitulate human-specific aspects of heart development, histogenesis and physiology is limited. Apart from ethical considerations, high cost and time demands associated with animal models, a major drawback is the interspecies variability at the physiological and genetic levels, which limits the translatability of respective findings to the treatment of humans ( Brandão et al, 2017 ; Davis et al, 2011a , b ; Wobus and Löser, 2011 ).…”
Section: Introductionmentioning
confidence: 99%